PENEGAKAN HUKUM PENYELESAIAN SENGKETA PEMILIHAN WALIKOTA DAN WAKIL WALIKOTA BLITAR TAHUN 2020 (STUDI KASUS DI BAWASLU KOTA BLITAR) - Zuhri, M. Saifuddin; Nurbaedah, Nurbaedah (Universitas Islam Kadiri, 2023)
The goal of this thesis is to discuss about the solution process of election dispute in general election watch committee (bawaslu) of Blitar Major based on constitution no 10 year 2016 about the second replacement on constitution no 1 year 2015 about the implementation of government’s rule replacing constitution no 1 year 2014, the rule of general election watch committee no 15 year 2017, and the rule of general election watch committee no 2 year 2020 about the solution process of major and vice major election. This research used empiric law research methodology. The research finding is that there was a protest from one of the candidates (lisminingsih – teteng rukmocondrono). They were disappointed on the document released by general election committee of Blitar city related to the numbers of independent electoral voters therefore they cannot enrol and participate as the independent candidate of blitar major in general election of Blitar major in 2020. Based on the protest above, general election committee of blitar city conducted hearing about it. The result of hearing is that the general election watch committee reject the protest by the candidate (lisminingsih – teteng rukmocondrono).